A Strong RFID Mutual Authentication Protocol Based on a Lightweight Public-key Cryptosystem - Zhicai Shi; Yongxiang Xia; Chaogang Yu (Institute of Advanced Engineering and Science, 2014)
RFID is a key technology that can be used to create the ubiquitous society. However, this technology may suffer from some serious threats such as privacy disclosure. In order to solve these secure problems we propose a strong mutual authentication protocol based on a lightweight public-key cryptosystem: NTRU. The protocol assures the confidentiality of the RFID system by encrypting the messages communicated between tags and readers and the freshness of the messages by using pseudorandom number generator. Otherwise, the protocol can also prevent replay attack, tracing, and eavesdropping effectively. This authentication protocol uses less computing and memory resources, and it is very suitable to some low-cost RFID systems. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4517